The effects of low-level laser therapy on the healing of bone defects in streptozotocin-induced diabetic rats: A histological and morphometric evaluation - Yıldırımtürk, Senem; Şirin, Yiğit; Tekkeşin Soluk, Merva; Gürler, Gökhan; Fırat, Deniz (Taylor & Francis Inc, 2017)
Background: The aim of the present study was to evaluate the effects of low-level laser therapy (LLLT) on the healing of bone defects in rats with streptozotocin (STZ)-induced DM. Methods: 28 male Sprague-Dawley rats were used in this study. 14 animals received a single dose of STZ intraperitoneally (65 mg/kg) to induce Type I DM, whereas others were injected only with sterile saline solution. Four weeks later, standard bone defects were created in the tibiae of rats. Surgical wounds in one group from each of the diabetic and non-diabetic animals were irradiated with diode laser for every other day for 4 weeks and they were described as DM + LLLT and CONT + LLLT groups, respectively. Remaining two groups received no laser treatment. New bone formation, osteoblast and blood vessel counts were calculated in histologic sections. Results: DM group had significantly smaller bone area and lower blood vessel count when compared to DM + LLLT, CONT and CONT + LLLT groups (p < 0.05 for each). CONT and CONT + LLLT groups had significantly larger bone area than DM + LLLT group (p < 0.05 for both). Conclusions: LLLT application promoted vascularization and new bone formation in animals with DM to a limited extent, since it was unable to support the healing process up to the level of non-diabetic animals.
WOS: 000413968900005
PubMed ID: 28622041
Keywords: Bone Defect Healing; Diabetes Mellitus; Low Level Laser Therapy; Rat